Anti-inflammation and anti-apoptosis effects of growth arrest-specific protein 6 in acute liver injury induced by LPS/D-GalN in mice - Wang,Qian (2020)
Abstract Purpose To investigate the effect of growth arrest-specific protein 6 (Gas6) on acute liver injury in mice and related mechanisms. Methods Thirty C57BL/6 (6-8 weeks old) mice were randomly divided into control, LPS/D-GalN, and LPS/D-GalN+Gas6 groups (10 mice in each group). The LPS/D-GalN group was intraperitoneally administered with LPS (0.25 mg/Kg) and D-GalN (400 mg/Kg) for 5h. The LPS/D-GalN+Gas6 group was intraperitoneally administered with rmGas6 one hour before intraperitoneal application of LPS/D-GalN. All subjects were sacrificed at 5 h for blood and tissue analysis. The expression of protein and mRNA was assessed by western blotting and RT-PCR, respectively. Results Compared with the control group, AST, ALT, IL-1β, TNF-α, IL-6 IL-10, MPO activity were increased in the LPS/D-GalN group. However, they were significantly inhibited by Gas6. Gas6 markedly suppressed the expression of apoptosis-related protein induced by LPS/D-GalN. Moreover, Gas6 attenuated the activation of the NF-κB signaling pathway in acute liver injury induced by LPS/D-GalN. Conclusions Gas6 alleviates acute liver injury in mice through regulating NF-κB signaling pathways. Gas6 can be a potential therapeutic agent in treating LPS/D-GalN-induced acute liver injury in the future.